OPTIMALISASI PERAN KORAMIL DALAM PEMBERDAYAAN WILAYAH PERTAHANAN GUNA MEMPERKOKOH KETAHANAN WILAYAH (Studi Di Koramil 2102/Cibinong Dan Koramil 2104/ Citeureup) - Asis Wanto (Universitas Gadjah Mada, 2013)
This paper explained the Koramil’s role as the frontline of the regional unity command and deserved special attention, due to the Koramil’s role as supporter and activator all over the regions to embodied the people’s defense. The qualitative data showed the Koramil in Bogor Regency encounter various obstacles in conducting their duties which made the lack of optimal services. These were due to the lack of transportation devices, communication devices, facilities and infrastructures, minimum budget support, and limited human resources and personnel.Keywords: Koramil, Establishment, and Regional Resilience.